Jacob Collier y Bizarrap: two cases of articulation between connectivity and homelike music production on YouTube (Revista Argentina de Musicología, 2022)
The following work carries out an approach to the music production strategies of both Jacob Collier (British multi-instrumentalist, composer, music producer and Youtuber born in 1994) and Bizarrap (argentine DJ, music producer and composer born in 1998). We highlight the aspects that show a configuration of music production-diffusion devices characterized by the combination of homelike techniques of music interpretation, recording, edition, and mixing with the utilization of the YouTube platform as a medium for public diffusion.In the Introduction there is a reference to the theoretic background that is taken as a reference for this approach. The second section consists of a description of the characteristics of YouTube as a scenario for the development of activities linked to the production, diffusion and consumption of popular music. In the third section, biographical information about both producers is offered and the contents of their YouTube channels are described and commented. In the last section the results of a comparative work are offered and a few provisional conclusions are drawn, looking forward to guide upcoming inquiries regarding music production and diffusion through digital platforms.
Keywords: Jacob Collier; Bizarrap; YouTube; music production and diffusion